Les dialogues de Walter Pater avec Platon : le philosophe et l’amoureux - Anne-Florence Gillard-Estrada (Cahiers Victoriens et Edouardiens)
This paper attempts to re-read Walter Pater’s first articles in the light of their Platonic intertextuality. Thanks to untranslated Greek excerpts, Pater aimed at legitimizing the Platonic discourse on love and on male beauty which was then being obliterated by Plato’s translator, Benjamin Jowett. However, Pater’s divergence from Plato is often underestimated. He shunned the Platonic distrust of the body, the senses and the ‘colours’ of the world, and he never accepted the Platonic primacy of the realm of Ideas. And in his essays on Plato, collected in Plato and Platonism (1895), he took up the aesthetics and the principles formulated in The Renaissance (1873). In his very personal reconstruction of Plato, Pater thus reasserted the role given to the sensible and the visible.